Os 3Vs das cidades criativas e a sua relação com o desenvolvimento econômico : proposta de indicador de criatividade para as cidades brasileiras - Stein, Natália Branco (2022)
The objective of this research was to systematize information about the discussion on the rise of creativity in the economy, indicating how it can be associated with the theme of urban economy, based on creative cities and its relationship with economic development. To fulfill this purpose, this research is divided into three specific objectives, presented from three articles. The first, entitled “The evolution of creativity participation in the economy”, aims to investigate the events and socioeconomic factors resulting from the phases of the Industrial Revolution that may have contributed to the greater manifestation of creativity in the economy in recent years, identifying the origin of the formation of creative cities. Based on a theoretical review, the social, economic and urban consequences of the first phase of the Industrial Revolution until the post-industrial phase were verified, relating such moments to studies in the field of psychology that identify the sources of stimulation or inhibition of creativity. The second article entitled “The 3Vs of Brazilian creative cities: a proposal for an indicator of creativity for the selected cities” intends to identify Brazilian creative cities through the construction of a Creativity Index that measures Cultural Vitality, Economic Vigor and Viability of the Environment (3Vs) of the core cities of large urban concentrations in Brazil. Based on an extensive theoretical review and the application of Confirmatory Factor Analysis, the appropriate variables were selected that were associated with the respective dimensions of the index. The third and final article, entitled “Creative cities and economic development: a controversial relationship”, aims to verify if the factors that form the Creativity Index of the previous article can explain the level of economic development of Brazilian cities, based on the application of Structural Equation Models. The relationship of each dimension individually with economic development is analyzed and, later, it is verified whether the set of the three dimensions produces markedly positive impacts on economic development. The research results indicate that throughout the history of humanity, creativity had its moments of inhibition and stimulation, contributing in an ascending way to the evolution of history. Economic and social changes broke the boundaries of manufacturing activity, forming creative districts and cities. The cities with the greatest potential to be creative identified in the second article are those located mainly in the Southeast and South regions of the country, also revealing regional inequality in terms of local creativity. This pattern, which associates creative cities with places of greater economic development, cannot be validated in the research, as the global model that tested the relationship of the set of 3Vs with economic development did not produce significant results.